The first modern risk : workplace accidents and the origins of European social states / Julia Moses. - Moses, Julia, 1979- (Studies in legal history., 2018)
During the late nineteenth century, many countries across Europe adopted national legislation that required employers to compensate workers injured or killed in accidents at work. These laws suggested that the risk of accidents was inherent to work and not due to individual negligence. By focusing on Britain, Germany, and Italy during this time, Julia Moses demonstrates how these laws reflected a major transformation in thinking about the nature of individual responsibility and social risk. The First Modern Risk illuminates the implications of this conceptual revolution for the role of the state in managing problems of everyday life, transforming understandings about both the obligations and rights of individuals. Drawing on a wide array of disciplines including law, history, and politics, Moses offers a fascinating transnational view of a pivotal moment in the evolution of the welfare state.